Estimation Of Color Change Of Maxillofacial Silicone Elastomer After Artificial Aging (Mustansiria Dental Journal, 2022)
Background: Silicone elastomers are the most widely used maxillofacial materials, however, it is far away from ideal and still progresses through many improvements for replacing the facial defect, maxillofacial prostheses need renewed as early as six months and can last up to 24 months. The color change is the most essential cause for remaking new prostheses.Aim: The purpose of this study was to assess the color stability of maxillofacial elastomers throughout aging of about one year.Materials and methods: Ten specimens were prepared from Room Temperature Vulcanazation (RTV) VerSilTal (VST-06) maxillofacial silicone and pigmented using rayon the flocking, the specimens were tested using the color-ometer device before and after subjecting to 46,146, and 317h accelerated weathering. The data were collected, analyzed, and compared using SPSS (V-18) via t-test, accomplished in confidence % 95 and significant P-Value of  (p ≤ 0.05).Results: Statistical t-test showed that the values of color changes differed among the tested groups (P≤ 0.05). The red wave value increased throughout weathering progress while the green and blue waves were decreased.Conclusions: This study presented that the color degradation may take place in VST-06 VerSilTal (room temperature vulcanization) silicone elastomers after it was exposed to 46h accelerated weathering and this degradation increased over time.